2015
DOI: 10.1002/chem.201502983
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Binding in the Active Site of Histone Demethylase JMJD2A and the Role of the Protein Environment

Abstract: JMJD2A catalyses the demethylation of di- and trimethylated lysine residues in histone tails and is a target for the development of new anticancer medicines. Mechanistic details of demethylation are yet to be elucidated and are important for the understanding of epigenetic processes. We have evaluated the initial step of histone demethylation by JMJD2A and demonstrate the dramatic effect of the protein environment upon oxygen binding using quantum mechanics/molecular mechanics (QM/MM) calculations. The changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 83 publications
(150 reference statements)
5
20
0
Order By: Relevance
“…This dioxygen binding plays a critical role and shows a strong dependence on the protein environment [ 10 ]. According to the model presented [ 10 , 34 , 35 ], ROS could directly affect this process. Another possibility is modifications of proteins that affect the activity of KDMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dioxygen binding plays a critical role and shows a strong dependence on the protein environment [ 10 ]. According to the model presented [ 10 , 34 , 35 ], ROS could directly affect this process. Another possibility is modifications of proteins that affect the activity of KDMs.…”
Section: Discussionmentioning
confidence: 99%
“…The JmjC-type KDMs are one group of α-ketoglutarate-dependent oxygenases that catalyze a remarkably diverse range of oxidative reactions [ 9 ]. The JmjC-type KDMs remove methyl groups on lysine in the specific amino acid stretches of histones, and the selectivity of substrates is determined by the structure of the JmjC domain and also the dynamics of the amino acid sequence near the JmjC domain [ 10 , 11 ]. KDMs also distinguish the number of methyl groups attached to lysine [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8b, 9] The LSD family of enzymes comprises two enzymes named LSD1 andL SD2, which contain FADa sacofactor and only accept di-and monomethylated lysinesa ss uitable substrates. The a-ketoglutarate cofactor 4 is incorporatedt ot he active site to give rise to intermediate 5.T his preparation step is followed by activation of the metallic site by binding to one molecule of oxygen to yield af erric superoxo adduct 6,i nw hich only one oxygen atom is bound to the metallicc enter.P aton et al [17] have shown that in JMJD2A the O 2 -Fe interaction accountsf or half the total interaction energy at the mosts table quintet state. These enzymesc an be classified in different subfamilies JMJDn,i nw hich n = 1-8.…”
Section: Introductionmentioning
confidence: 99%
“…[53] Later the protein contributions to binding have been quantified also for IPNS, MIOX, and JMJD2A. [74][75][76] These results show a consistent stabilization, see Figure 9. There are two major contributions: 1) the van der Waals interactions between the bound dioxygen and the protein atoms and (2) electrostatic effects on a charge transfer from iron(II) to oxygen to form iron(III)-superoxide.…”
Section: Reaction Energy Profiles -Electrostatic and Van Der Waals Inmentioning
confidence: 60%